(untitled) (Acta Scientiarum. Health Sciences, 2015)
Food is essential for the promotion of health and the low intake of fruits and vegetables (FV) is a risk factor for chronic non-communicable diseases. Current descriptive and cross-sectional study evaluated the consumption of FVby teenagers in Penha, Santa Catarina State, Brazil, and its relation to nutritional and socioeconomic status. The study involved 361 adolescents who were assessed through a self-administered questionnaire featuring demographic and socioeconomic variables. Body Mass Index was applied to assess nutritional status coupled to a Food Frequency Questionnaire for Adolescents for the consumption of FV. The sum of the responses was compared to the recommendations of the World Health Organization (>400 g day-1), ranking them as adequate or inadequate. Results showed the prevalence of males (51%), adherence to physical activity (71%) and eutrophy (65%). Nonetheless, only 32% met the minimum recommendations of FV daily consumption which revealed an inverse association with the consumption of soft drinks. Taking snacks at school makes most teenagers consume less FV. Although no association between the consumption of FV, nutritional and socioeconomic status was found, the consumption of FV is below the recommendations.